Torque ripple reduction of synchronous reluctance machines: Optimal slot/pole and flux-barrier layer number combinations. Issue 1 (5th January 2015) - Wang, K.; Zhu, Z.Q.; Ombach, G.; Koch, M.; Zhang, S.; Xu, J.
Abstract : Purpose: – The purpose of this paper is to investigate the influence of stator and rotor pole number combinations together with the flux-barrier layers number on the performance of synchronous reluctance machine with emphasis on output torque capability and torque ripple. Design/methodology/approach: – AC synchronous reluctance machine (SynRM) or permanent magnet assisted SynRM presently receives a great deal of interest, since there is less or even no rare-earth permanent magnet in the rotor. Most of SynRM machines employ a stator that is originally designed for a standard squirrel cage induction motor for a similar output rating and application, or the SynRM machine with 24-slot, four-pole are often directly chosen for investigation in most of the available literature. Therefore, it is necessary to investigate the influence of stator and rotor pole number combinations together with the flux-barrier layers number on the performance of SynRM machine with emphasis on output torque capability and torque ripple. Findings: – The average torque decreases with the increase of the pole numbers but remain almost constant when employing different stator slot numbers but with the same pole number. In addition, the torque ripple decreases significantly with the increase of the stator slot number. The machine with double-layer flux-barrier in the rotor has the biggest average torque, while the machines with three- and four-layer flux-barrier in the rotor have almost the same average torque but their value is slightly smaller than that of machine with double-layer flux-barrier. However, the machine with three-layer flux-barrier has the lowest torque ripple but the highest torque ripple exists in the machine with double-layer flux-barrier. Research limitations/implications: – The purely sinusoidal currents are applied in this analysis and the effects of harmonics in the current on torque ripple are not considered in this application. Originality/value: – This paper has analyzed the torque ripple and average torque of SynRMs with considering slot/pole number combinations together with the flux-barrier number.